Efeito protetor da lectina de sementes de Moringa oleifera lamarck na cistite hemorrágica induzida por ifosfamida em camundongos - Sousa, Kályan Nogueira (2017)
A hemorrhagic cystitis is a side effect of antineoplastic agents belonging to the oxazaphosphorines group (ifosfamide and cyclophosphamide) and this occurs due to the formation of the urotoxic metabolite acrolein. Moringa oleifera Lamarck is a plant belonging to the family Moringaceae found mainly in the Northeast of Brazil. An isolated molecule of its Mo-CBP4 (Mo: Moringa oleifera and CBP: "chitin-binding protein") seeds has potent anti-inflammatory and antinociceptive activities, therefore the present study had as objective to evaluate the effect of Mo-CBP4 in hemorrhagic cystitis induced by ifosfamide. Hemorrhagic cystit was induced in female swiss mice (n=6) by administration of ifosfamide (400 mg/kg i.p.) and as negative control group the animals were treated with sterile saline solution (NaCl 0.9%, i.p.). In the other experimental groups of animals treated with Mesna (80 mg/kg i.p.) and Mo-CBP4 (10, 20 and 40 mg/kg e.v.) 30 min before, 4 h and 8 h after an ifosfamide injection. After 12 hours of ifosfamide administration, the animals were euthanized and collected as bladders to evaluate edema, hemorrhage, myeloperoxidase activity (MPO), differential leukocyte count (neutrophils and lymphocytes), histopathology, cytokine (IL-1β, IL-8 and TNF-α), COX-2 immunoblotting and quantitation of glutathione (GSH). Statistical analysis was performed using the ANOVA/Bonferroni or Kruskal Wallis/Dunn tests; Values of P <0.05 were considered statistically significant. Initially, Mo-CBP4 at doses of 10, 20 and 40 mg/kg promoted a reduction in bladder weight in 24.29%, 50.80%, 61.18% respectively. It had a protective effect in macroscopic and histopathological analysis, where Mo-CBP4 at doses of 20 and 40 mg/kg for preventing edema formation, but only a dose of 40 mg/kg was effective in preventing bleeding and lectin at the dose of 10 mg/kg had no effect on the formation of both parameters. Mo-CBP4 (20 mg/kg) prevented vascular permeability (60%) and reduced the MPO activity (85%). In the differential leukocyte count also promoted a reduction in the number of lymphocytes (75%) and neutrophilis (77%) and was able to prevent the release of inflammatory cytokines IL-1β (26.69%), IL-8 (53.16%) and TNF-α (19.75%). In addition, it promoted reduction of COX-2 immunostaining and maintained the GSH concentration (80.55%) similar to that of normal animals. Thus, the set of results demonstrated that Mo-CBP4 has anti-inflammatory action in the experimental hemorrhagic cystitis induced by ifosfamide acting on the prevention of edema formation, decreasing leukocyte migration, reducing of inflammatory cytokines concetrations (IL-1β, IL-8 and TNF-α), reduction of COX-2 immunolabeling and inhibiting reduction of concentration from GSH.